Enhancing MicroRNA Activity through Increased Endosomal Release Mediated by Nigericin - Esteban A. Orellana; Ahmed M. Abdelaal; Loganathan Rangasamy; Srinivasarao Tenneti; Sunghyun Myoung; Philip S. Low; Andrea L. Kasinski (Elsevier, 2019)
The therapeutic promise of small-RNA therapeutics is limited, not only by the lack of delivery vehicles, but also by the inability of the small RNAs to reach intracellular compartments where they can be biologically active. We previously reported successful delivery of functionally active miRNAs via receptor-mediated endocytosis. This type of targeted therapy still faces a major challenge in the delivery field: endosomal sequestration. Here, a new method has been developed to promote endosomal escape of delivered miRNA. The strategy relies on the difference in solute contents between nascent endosomes and the cytoplasm; early endosomes are rich in sodium ions, whereas the intracellular fluid is rich is potassium ions. Exploiting this difference through favoring the influx of potassium into the endosomes without the exchange of osmotically active sodium, results in an osmotic differential leading to the endosomes swelling and bursting. One molecule that is able to exchange potassium for an osmotically inactive hydrogen ion is the ionophore nigericin. Through generating an intramolecular miRNA delivery vehicle, containing a ligand, in this case folate and nigericin, we enabled the escape of folate-RNA conjugates from their entrapping endosomes into the cytoplasm where they bound the RNA-induced silencing complex and activated the RNAi response. Keywords: microRNA, miR-34, nigericin, endosomal escape, folate, ligand, delivery, folate-conjugates